Hypermethylation of ACADVL is involved in the high-intensity interval training-associated reduction of cardiac fibrosis in heart failure patients - Chih-Chin Hsu; Jong-Shyan Wang; Yu-Chiau Shyu; Tieh-Cheng Fu; Yu-Hsiang Juan; Shin-Sheng Yuan; Chao-Hung Wang; Chi-Hsiao Yeh; Po-Cheng Liao; Hsin-Yi Wu; Pang-Hung Hsu (Journal of Translational Medicine, 2023)
Abstract Background Emerging evidence suggests that DNA methylation can be affected by physical activities and is associated with cardiac fibrosis. This translational research examined the implications of DNA methylation associated with the high-intensity interval training (HIIT) effects on cardiac fibrosis in patients with heart failure (HF). Methods Twelve HF patients were included and received cardiovascular magnetic resonance imaging with late gadolinium enhancement for cardiac fibrosis severity and a cardiopulmonary exercise test for peak oxygen consumption ( $$\normalsize \tt V$$ V O2peak). Afterwards, they underwent 36 sessions of HIIT at alternating 80% and 40% of $$\normalsize \tt V$$ V O2peak for 30 min per session in 3–4 months. Human serum from 11 participants, as a means to link cell biology to clinical presentations, was used to investigate the exercise effects on cardiac fibrosis. Primary human cardiac fibroblasts (HCFs) were incubated in patient serum, and analyses of cell behaviour, proteomics (n = 6) and DNA methylation profiling (n = 3) were performed. All measurements were conducted after completing HIIT. Results A significant increase (p = 0.009) in $$\normalsize \tt V$$ V O2peak (pre- vs. post-HIIT = 19.0 ± 1.1 O2 ml/kg/min vs. 21.8 ± 1.1 O2 ml/kg/min) was observed after HIIT. The exercise strategy resulted in a significant decrease in left ventricle (LV) volume by 15% to 40% (p < 0.05) and a significant increase in LV ejection fraction by approximately 30% (p = 0.010). LV myocardial fibrosis significantly decreased from 30.9 ± 1.2% to 27.2 ± 0.8% (p = 0.013) and from 33.4 ± 1.6% to 30.1 ± 1.6% (p = 0.021) in the middle and apical LV myocardium after HIIT, respectively. The mean single-cell migration speed was significantly (p = 0.044) greater for HCFs treated with patient serum before (2.15 ± 0.17 μm/min) than after (1.11 ± 0.12 μm/min) HIIT. Forty-three of 1222 identified proteins were significantly involved in HIIT-induced altered HCF activities. There was significant (p = 0.044) hypermethylation of the acyl-CoA dehydrogenase very long chain (ACADVL) gene with a 4.474-fold increase after HIIT, which could activate downstream caspase-mediated actin disassembly and the cell death pathway. Conclusions Human investigation has shown that HIIT is associated with reduced cardiac fibrosis in HF patients. Hypermethylation of ACADVL after HIIT may contribute to impeding HCF activities. This exercise-associated epigenetic reprogramming may contribute to reduce cardiac fibrosis and promote cardiorespiratory fitness in HF patients. Trial registration: NCT04038723. Registered 31 July 2019, https://clinicaltrials.gov/ct2/show/NCT04038723 .